Lute Music in the Area of Contemporary Slovakia in the Period of Renaissance Jean Baptista Besard - Thesaurus Harmonicus - Hottmar, Michal (Communications - Scientific Letters of the University of Zilina, 2005)
The article analyses the issue of occurrence of lute music, its repertoire, players, and composers connected with the area of Slovakia in the age of humanism.
Keywords: no keywords